2018
DOI: 10.1021/acsomega.8b02870
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Cu(II)-Selective Electrode in the Polyvinyl Chloride Matrix Utilizing Mechanochemically Synthesized Rhodamine 6g as an Ionophore

Abstract: A Cu(II)-selective electrode has been fabricated by utilizing a mechanochemically synthesized copper-specific ionophore “L” embedded in a poly(vinyl chloride) membrane. 2-Nitrophenyloctylether and sodium tetraphenylborate have been used as a plasticizer and as a solvent mediator, respectively, and found to be enhancing the sensitivity of the fabricated ion-selective electrode (ISE). A range of membranes (S1–S7) with varying compositions were casted and investigated in ISE. Results revealed an excellent Nernsti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 54 publications
3
11
0
1
Order By: Relevance
“…Paul et al fabricated a Cu 2+ -selective electrode utilizing an ionophore mechanochemically synthesized from rhodamine 6G hydrazide and tridentate zwitterion. 144 The described Cu 2+ -selective electrode exhibited a response slope of 29.3 mV/decade and a lower detection of 5 μM in the pH range from 3.0 to 7.5. The logarithmic selectivity coefficients over the main interfering ions, such as Pb 2+ , Zn 2+ , Ni 2+ , Co 2+ , Cd 2+ , and Fe 2+ , were above −3.0.…”
Section: Mittal Et Al Synthesized and Tested An Imine-based Ligand (E...mentioning
confidence: 93%
See 1 more Smart Citation
“…Paul et al fabricated a Cu 2+ -selective electrode utilizing an ionophore mechanochemically synthesized from rhodamine 6G hydrazide and tridentate zwitterion. 144 The described Cu 2+ -selective electrode exhibited a response slope of 29.3 mV/decade and a lower detection of 5 μM in the pH range from 3.0 to 7.5. The logarithmic selectivity coefficients over the main interfering ions, such as Pb 2+ , Zn 2+ , Ni 2+ , Co 2+ , Cd 2+ , and Fe 2+ , were above −3.0.…”
Section: Mittal Et Al Synthesized and Tested An Imine-based Ligand (E...mentioning
confidence: 93%
“…Paul et al fabricated a Cu 2+ -selective electrode utilizing an ionophore mechanochemically synthesized from rhodamine 6G hydrazide and tridentate zwitterion . The described Cu 2+ -selective electrode exhibited a response slope of 29.3 mV/decade and a lower detection of 5 μM in the pH range from 3.0 to 7.5.…”
Section: Sensor Materialsmentioning
confidence: 99%
“…The chemosensors worked well for Cu 2+ detection in filter paper strips as a part of on-field device application (Figure C). In another study, they prepared a previously reported chromophore ( 40 ) by hand-grinding a mixture of rhodamine 6G hydrazide ( 36 ) and a zwitterion ionophore ( 39 ) (Figure D) . This time, a 5 h reflux in methanol could be averted, and the product was obtained in just 5 min of grinding.…”
Section: Mechanochemical Synthesis and Modification Of Fluorophores F...mentioning
confidence: 99%
“…In another study, they prepared a previously reported chromophore (40) 41 by hand-grinding a mixture of rhodamine 6G hydrazide (36) and a zwitterion ionophore (39) (Figure 2D). 42 This time, a 5 h reflux in methanol could be averted, and the product was obtained in just 5 min of grinding. The chromophore was incorporated into a PVC matrix along with 2-nitrophenyloctyl ether (NPOE) as a plasticizer to fabricate an ion-selective electrode which is specific for Cu(II) ions.…”
Section: Mechanochemical Synthesis and Modification Of Fluorophores F...mentioning
confidence: 99%
“…Due to the discharge of industrial effluents into natural waters, heavy metal ions adversely affect environment and human health (2). Among the heavy metals, Fe and Cu are the first and second most widely used industrial metals worldwide (3). Fe 3+ plays a significant role in various metabolic processes including oxygen transport, enzyme catalysis, DNA and RNA synthesis, and hemoglobin synthesis (4).…”
Section: Introductionmentioning
confidence: 99%